Thyroid dysfunction and insulin resistance in end‐stage renal disease patients before and 1 year after starting maintenance hemodialysis: A prospective multicenter study. Issue 2 (8th December 2021) - Tawfik, Mona; Fathy, Noha; Mousa, Amany A.; Ghonem, Mohamed; Abdelsalam, Mostafa
Abstract: Background: Thyroid dysfunction and insulin resistance (IR) are common findings in patients with ESRD. We aimed to evaluate thyroid dysfunction and IR in ESRD before and after 1 year of starting hemodialysis (HD). Methods: This was a prospective study that recruited newly starting HD patients who fulfilled the inclusion criteria. Patients were evaluated for TSH, free T4, free T3, fasting insulin, fasting glucose, HOMA‐IR, serum ferritin, and hs‐CRP levels before starting their first dialysis session and after 1 year of regular HD. Results: Eighty‐one patients have completed the 1‐year follow‐up period. After 1 year of regular HD, there were statistically significant increments of hs‐CRP, serum ferritin, and TSH levels. On the other hand, fasting insulin level and HOMA‐IR showed statistically significant increments after 1 year of starting HD. After 1 year of regular HD, TSH level showed a positive correlation with hs‐CRP and serum ferritin level, while free T3 was negatively correlated with HOMA‐IR. On the other hand, there was a significant positive correlation between HOMA‐IR, hs‐CRP, and serum ferritin levels, while HOMA‐IR was negatively correlated with Kt/V. Conclusions: This study suggests overlapping complex pathogenesis of thyroid dysfunction, chronic inflammation, and IR in chronic HD patients.